Change in seed viability of commercial maize hybrids during storage - Perić Sanja; Stevanović Milan; Mladenović Marko; Popović Aleksandar; Kovačević Aleksandar; Grčić Nikola (Selekcija i Semenarstvo)
The production and processing of commercial seeds place significant emphasis on seed quality, with germination rates being a critical determinant of market performance. A major challenge in corn seed production and processing is maintaining optimal storage conditions to preserve germination and vigor over time. In the Republic of Serbia, certified corn seeds must adhere to specific germination standards as outlined by regulatory guidelines. Given that germination rates decline during storage, routine germination testing at accredited laboratories is imperative. The aim of this study is to evaluate the changes in total germination and vigor of certified hybrid corn seed over a five-year period. Annual germination tests were conducted from 2018 to 2022 for three commercial maize hybrids (ZP 704, ZP 873, and ZP 600). The standard "between the paper" germination test was utilized, and results for each hybrid were reported as averages from the tested lots. Initial testing conducted in 2018 revealed the highest average values for total germination and vigor across three hybrids: ZP 704 (98.8%/98.8%), ZP 873 (100%/100%), and ZP 600 (98.3%/98.3%). By 2020, a slight decrease in both germination and vigor was observed for all hybrids, with equal values for germination energy and total germination. By the end of the study in 2022, the average total germination for all hybrids remained above 90%, specifically ZP 704 (93.7%), ZP 873 (94%), and ZP 600 (96%). Notably, while the vigor of hybrids ZP 704 (92.7%) and ZP 873 (88%) was lower than their total germination rates, hybrid ZP 600 demonstrated consistent results, with both total germination and vigor at 96%. The findings indicate that seed storage conditions were in accordance with regulations, as evidenced by acceptable overall germination rates for all hybrids at the end of the test period.